2010
DOI: 10.2139/ssrn.1679666
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and Financial Satisfaction in Israel: Effects of Religiosity, Ethnicity, and War

Abstract: We analyze individual satisfaction with life as a whole and satisfaction with the personal financial situation for Israeli citizens of Jewish and Arab descent. Our data set is the Israeli Social Survey (2006). We are especially interested in the impact of the religions Judaism, Islam and Christianity, where we are able to differentiate between individuals who vary in religiosity between secular and ultra-orthodox. We find a significant effect of religiosity on happiness. With respect to Jewish families it is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Other scholars reported lower life satisfaction of immigrants in the US (Bartram, 2011) and in Europe (Safi, 2010) compared to natives. Few studies found differences between groups of immigrants to the same country depending on origin (Magee and Umamahesvar, 2011;Van Praag et al, 2010).…”
Section: Cultures Of Life Satisfaction and Their Consequencesmentioning
confidence: 99%
“…Other scholars reported lower life satisfaction of immigrants in the US (Bartram, 2011) and in Europe (Safi, 2010) compared to natives. Few studies found differences between groups of immigrants to the same country depending on origin (Magee and Umamahesvar, 2011;Van Praag et al, 2010).…”
Section: Cultures Of Life Satisfaction and Their Consequencesmentioning
confidence: 99%
“…The challenges elders and families face might be similar, but the solutions tend to be different. Thus, studying older people in diverse groups can add to our understanding of the richness and complexity of aging, family relations, and well-being (e.g., Shmotkin & Hadari, 1996;Van Praag, Romanov, & Ferrer-i-Carbonell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together the cited works suggest that the larger the FS of an individual, the happier he/she is. In other words: the individual satisfaction with the financial situation of the household is a component of or LS of the person (Peiró, ; Van Praag, Romanov, & Ferrer‐i‐Carbonell, ), and thus the two are positively and substantially correlated.…”
Section: Related Literaturementioning
confidence: 99%
“…Van Praag et al. () study the impact of the last Lebanon war on Israeli Jewish and Muslims, and conclude that the former are significantly more satisfied with their life than the latter and that the Israeli victory raised the happiness of the Jewish, while it did not affect that of the Muslims. Both these papers provide evidence of the fact that being member of a discriminated minority actually decreases (or at least does not foster) LS.…”
Section: Related Literaturementioning
confidence: 99%